2021
DOI: 10.22175/mmb.11705
|View full text |Cite
|
Sign up to set email alerts
|

Differential Abundance of Mitochondrial Proteome Influences the Color Stability of Beef <i>Longissimus Lumborum</i> and <i>Psoas Major</i> Muscles

Abstract: Mitochondrial functionality affects muscle-specific beef color stability. Nonetheless, the relationship between mitochondrial proteome and muscle-specific beef color stability is yet to be examined. Therefore, the objective of the present study was to differentiate the proteomes of mitochondria from beef longissimus lumborum (LL; color-stable muscle) and psoas major (PM; color-labile muscle) steaks during retail display. LL and PM muscles from 7 beef carcasses (USDA Choice; 48 h postmortem) were fabricated int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…Among the differential proteins in the TCA cycle, CS, MDH2, and SUCLG2 were more abundant in PM muscles compared with LL (Yu et al, 2017b(Yu et al, , 2018Ramanathan et al, 2021). These proteins contribute to the production of ATP by oxidative phosphorylation in PM muscles, resulting in the production of ROS and, consequently, oxidative and color instability.…”
Section: Tca Cycle and Carbohydrate Metabolism Enzymesmentioning
confidence: 96%
See 1 more Smart Citation
“…Among the differential proteins in the TCA cycle, CS, MDH2, and SUCLG2 were more abundant in PM muscles compared with LL (Yu et al, 2017b(Yu et al, , 2018Ramanathan et al, 2021). These proteins contribute to the production of ATP by oxidative phosphorylation in PM muscles, resulting in the production of ROS and, consequently, oxidative and color instability.…”
Section: Tca Cycle and Carbohydrate Metabolism Enzymesmentioning
confidence: 96%
“…NADH is a crucial component of enzymatic and nonenzymatic MRA (Echevarne et al, 1990;Mancini and Hunt, 2005;Kim et al, 2006;Ramanathan et al, 2021) and MPC2 protein, could contribute to the production of reducing equivalents, including NADH. At the same time, 2-oxoglutarate dehydrogenase mitochondrial isoform X1 (OGDH) plays a role in catalytic conversion of 2-oxoglutarate to succinyl-CoA, CO 2 , and NADH (Qi et al, 2011;Zhai et al, 2019).…”
Section: Tca Cycle and Carbohydrate Metabolism Enzymesmentioning
confidence: 99%
“…Many shreds of evidence also suggest an association between mitochondria attributes and embryo implantation as well as development affecting fertility and productivity potential in bovines [27][28][29], in addition to pregnancy-related disorders in women [30]. Moreover, mitochondrial functionality and differential mitochondrial proteome pro les also in uence meat quality [31]. Even high-altitude disorders in cattle affect the mitochondrial integral function, which impacts beef quality [32].…”
Section: Introductionmentioning
confidence: 99%
“…Previous and ongoing proteomics and metabolomics work in both color and tenderness studies have indicated that specific proteins and metabolites associated with various biological and metabolic pathways are correlated with beef color stability (Joseph et al, 2012;Canto et al, 2015;Yu et al, 2017;Nair et al, 2018b;Nair et al, 2018a;Yu et al, 2019b;Ramanathan et al, 2020a;Wu et al, 2020;Ramanathan et al, 2021) and beef tenderness traits (D'Alessandro et al, 2012;Picard et al, 2014;Picard and Gagaoua, 2017;King et al, 2019;Malheiros et al, 2019;Antonelo et al, 2020;Picard and Gagaoua, 2020;Gagaoua et al, 2021). Many of these specific systems and their products have been found to be correlated with both color stability and tenderness attributes indicating potential mechanisms behind relationships these traits.…”
Section: Introductionmentioning
confidence: 99%
“…Beef color stability is a factor impacted by numerous intrinsic and extrinsic factors. Color stability is impacted by muscle source (McKenna et al, 2005;King et al, 2011b;Joseph et al, 2012;Canto et al, 2016;Nair et al, 2018a), physiological age and sex (Faustman et al, 1992;Cho et al, 2015), ultimate pH (Page et al, 2001;McKeith et al, 2016;Zhang et al, 2018;Ramanathan et al, 2020a), myoglobin (Suman and Joseph, 2013;, mitochondrial abundance and functionality (Seyfert et al, 2006;Mitacek et al, 2019;Wu et al, 2020;Ramanathan et al, 2021), metmyoglobin reducing activity (Madhavi and Carpenter, 1993;Bekhit and Faustman, 2005;Seyfert et al, 2006), oxygen consumption (Tang et al, 2005a), aging time and method (Mancini and Ramanathan, 2014;Wyrwisz et al, 2016;Callahan et al, 2017;Nair et al, 2018a), packaging and display characteristics (Cooper et al, 2016;Cooper et al, 2017;Cooper et al, 2018;Mitacek et al, 2018), and oxidation (Greene and Price, 1975;Faustman and Cassens, 1990;Faustman et al, 1999;Lynch and Faustman, 2000;Faustman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%